Bioboxes: standardised containers for interchangeable bioinformatics software. Issue 1 (December 2015) - Belmann, Peter; Dröge, Johannes; Bremges, Andreas; McHardy, Alice; Sczyrba, Alexander; Barton, Michael
Abstract Software is now both central and essential to modern biology, yet lack of availability, difficult installations, and complex user interfaces make software hard to obtain and use. Containerisation, as exemplified by the Docker platform, has the potential to solve the problems associated with sharing software. We propose bioboxes: containers with standardised interfaces to make bioinformatics software interchangeable.